Exposure to inhalable dust and its cyclohexane soluble fraction since the 1970s in the rubber manufacturing industry in the European Union. Issue 6 (10th October 2007) - de Vocht, F; Vermeulen, R; Burstyn, I; Sobala, W; Dost, A; Taeger, D; Bergendorf, U; Straif, K; Swuste, P; Kromhout, H; ,
Abstract : Objectives: As exposures to airborne particulates in the European rubber industry might still be causing genotoxic risks, it is important to assess trends in levels of inhalable dust and its cyclohexane soluble fraction (CSF) between the 1970s and 2003. Methods: 13 380 inhalable and 816 respirable dust and 5657 CSF measurements, collected within the framework of the European Union Concerted Action EXASRUB, were analysed. Hierarchical mixed effects models were applied to assess exposure trends, taking into account between-factory, between-worker/location and day-to-day variances. Results: Geometric mean levels of inhalable dust and CSF exposure changed by −4 (range −5.8 to +2.9) and −3 (range −8.6 to 0) per year, respectively. Significant reductions in inhalable dust concentrations were found in all countries for handling of crude materials and mixing and milling (−7 to −4 per year), as well as for miscellaneous workers (−11 to −5 per year), while significant CSF exposure reductions were found in curing (−8.6 per year) and maintenance and engineering departments (−5.4 per year). Conclusion: These analyses suggest that on average exposure levels of inhalable dust and its CSF in the European rubber manufacturing industry have steadily declined. Most likely genotoxic risks have also lessened over time since exposure levels have decreased and the most toxic chemicals have been replaced. In addition to differences in exposure reductions and levels among various stages of the production process, large differences across countries were noted. These patterns should be taken into account in retrospective assessment of exposure for epidemiological studies assessing cancer risk in the rubber industry.